Modeling of the movement and stress distribution of a line-shaped item in a vortex - Ngin, Eric Cheong Soon (Nanyang Technological University, 2020)
The purpose of this project focuses on the movement of single and multiple nodes in a vortex. Vortex exists in the form of natural free vortex or forced vortex induced by external forces. Vortex is used in fluid applications ranging from industrial pumps to materials separator using vortex movement and also in the natural form of whirlpool or hurricane. Thus, it is of great importance to study vortex flow to know how it influences object motion in a vortex. Using ANSYS FLUENT, a physical model capable of simulating the movement of a line-shaped item in a vortex and analysing the stress distribution along the length direction of the item was developed. Further analysis of the movement of the object such as trajectory motion and force balance were done with MATLAB. The project was divided into 3 main parts. 1. Data of force vortex fluid flow consisting of velocity and position of the mesh nodes was obtained from the simulation of force vortex in ANSYS Fluent. 2. Numerical analysis of forces and stresses acting on the nodes of the object in vortex was done.3. Velocity of forced vortex at each position nodes in the vortex was built up based on actual data of forced vortex obtained from part 1. Then, based on formulation of forces interaction of the vortex and object, the trajectory of the object in vortex was built up based on varying independent variables such as the initial position and orientation of object which is the main focus of this research. Other variables include density, size, shape, initial velocity of object nodes as well as the spring constant of spring connecting the nodes.